A model for assessing the non-linguistic framing of conflict narratives: the case of interpreters in the Libyan warzone 2011. Issue 3 (2nd September 2019) - Alkhaldy, Muman
ABSTRACT: The performance of interpreters in wartimes is not always related to language mediation as it, in most cases, exceeds interpreting the performance of extra tasks. This excess increases the significance range of the roles of interpreters in framing the narratives of war zones. In order to examine this work, I have developed a new model (non-linguistic framing), which is developed to fulfil the gap regarding the issue of the framing of narratives in the work of war-zone interpreters. The model discusses the impact of the extra tasks that war-zone interpreters perform, as well as the range of selection they are allowed on framing conflicts on two main non-textual roles, which are (a) interpreters and gatekeeping, and (b) interpreters and suppression. The framework in this paper is based mainly on Mona Baker's understanding of narrative theory and framing theory and other studies submitted in the field. This article starts by elucidating languages at wars and the need for such a model, briefly explaining the data and the methodology used to collect the data, presenting my developed model, and ending with concluding remarks.